Intellectual Property Rights, Innovation and Technology Transfer: A Survey - Anja Breitwieser; Neil Foster-McGregor (The Vienna Institute for International Economic Studies (wiiw), 2012)
Following the conclusion of the TRIPS Agreement, much has been written on the potential costs and benefits of stronger Intellectual Property Rights (IPRs) protection in terms of its impact on innovation and technology transfer, as well as economic growth and welfare. This paper documents the development of IPR regimes within countries and internationally, before surveying the theoretical and empirical literature linking the protection of IPRs to economic growth, innovation and technology diffusion.
Keywords: O3; 330; intellectual property rights; economic growth; innovation; technology diffusion